(untitled) (Nativa, 2024)
ABSTRACT: To restore degraded floodplains with agroforestry systems (AFS), more ecological knowledge about native species is needed. This research aimed to evaluate the survival, growth, and biomass input of native trees planted and managed in an AFS to enrich a monoculture of Calophyllum brasiliense. The findings, which are encouraging for the future of agroforestry, revealed that available light did not limit survival and growth in these groups. The pioneers grew faster, although the greatest height was in Sesbania virgata, Schinus terebinthifolius, Handroanthus impetiginosus, Inga vera and Citharexylum myrianthum. However, the higher relative growth rates indicate that E. verna, P. grandiflorum, and Anadenanthera colubrina have grown more in the last 15 months than S. virgata. The three species with the largest canopy radius were S. terebinthifolius, I. vera and C. myrianthum, the most significant contribution of the phytomass supply during pruning was from S. virgata and S. terebinthifolius. Euterpe edulis and S. virgata intercropping supported the palm tree in overcoming climatic extremes between the lines of C. brasiliense. This research highlights the potential of AFS to innovate for a sustainable agricultural and forestry production future that aligns with ecological restoration requirements. Keywords: Atlantic Forest; forest landscape restoration; native tree; Euterpe edulis; agroforestry management. Espécies arbóreas para enriquecimento agroflorestal da monocultura de Calophyllum brasiliense Cambess em várzea RESUMO: Para restaurar planícies aluviais com sistemas agroflorestais (SAF), é necessário mais conhecimento ecológico sobre as espécies nativas. Esta pesquisa teve como objetivo avaliar a sobrevivência, o crescimento e o aporte de biomassa de arbóreas plantadas e manejadas em SAF para enriquecimento de uma monocultura de Calophyllum brasiliense. Foram avaliadas oito espécies pioneiras e oito não pioneiras, totalizando 375 árvores em oito parcelas de 216m². A luz disponível não limitou a sobrevivência e o crescimento nestes grupos. As pioneiras cresceram mais rápido, embora a maior altura tenha sido observada em Sesbania virgata, Schinus terebinthifolius, Handroanthus impetiginosus, Inga vera e Citharexylum myrianthum. Contudo, as maiores taxas de crescimento relativo indicam que E. verna, P. grandiflorum e Anadenanthera colubrina cresceram mais nos últimos 15 meses do que S. virgata. As três espécies com maior raio de copa foram S. terebinthifolius, I. vera e C. myrianthum, e a maior contribuição no aporte de fitomassa na poda foi de S. virgata e S. terebinthifolius. O consórcio de Euterpe edulis e S. virgata apoiou a palmeira a superar o estresse térmico e hídrico nas entrelinhas de C. brasiliense. Os SAF inovam para um futuro de produção agrícola e florestal sustentável alinhada com as exigências de restauração ecológica. Palavras-chave: Mata Atlântica; restauração da paisagem florestal; árvore nativa; Euterpe edulis; manejo agroflorestal.